Ions play different roles in virus removal caused by different NOMs in UF process: Removal efficiency and mechanism analysis. (February 2023) - Ren, Zixiao; Cao, Haiyan; Desmond, Peter; Liu, Bingsheng; Ngo, Huu Hao; He, Xu; Li, Guibai; Ma, Jun; Ding, An
Abstract: In this study, we investigated the effect of different compositions of aquatic natural organic matter (NOM) and ions on virus removal by ultrafiltration (UF). MS2 bacteriophage was used as a surrogate. Humic acid (HA) improved the MS2 removal rate from 1.95 ± 0.09 LRV to 2.40 ± 0.03 LRV at the HA dosage of 9 mg/L through the combined mechanisms of size exclusion, electrostatic repulsion and hydrophobicity. MS2 removal rate further increased to 3.10 ± 0.05 LRV by 10 mmol/L Na + dosage and 3.19 ± 0.12 LRV by Ca 2+ 1 mmol/L in the HA-containing UF system. Size exclusion turned into the dominant virus removal mechanism according to the results of the fouling model fitting and the weakening of electrostatic repulsion and hydrophobicity. The complexation of Ca 2+ also played a role in MS2 removal based on the analysis of interaction force. MS2 removal rate by bovine serum albumin (BSA) was poor, which was 2.07 ± 0.06 LRV at the BSA dosage of 9 mg/L. Hydrophobicity was greatly reduced and the dominant virus removal mechanisms were size exclusion and electrostatic repulsion. 10 mmol/L Na + in the presence of BSA deteriorated MS2 removal rate to 2.02 ± 0.07 LRV by the weakening of electrostatic repulsion, hydrophobicity and size exclusion. Electrostatic repulsion severely decreased by 1 mmol/L Ca 2+ and the enhanced adsorption barrier represented competitive adsorption of Ca 2+ by BSA and MS2 contributed for MS2 removal further decline (1.99 ± 0.05 LRV). Complex components in water will have different effects on virus removal due to their properties and interactions. This study can provide references for selecting more efficient water treatment methods according to the different compositions of raw water in actual water treatment applications during the UF process. Moreover, the retention of virus by UF can be predicted based on our study results. Graphical abstract: Image 1 Highlights: Effect and mechanism of water environment on virus removal by UF were investigated. Organic improved MS2 removal in UF by size exclusion and electrostatic repulsion. Ions further improved MS2 removal in the HA system by size exclusion. Light membrane fouling and electronegativity caused by BSA led to poor MS2 removal. Competitive adsorption of Ca 2+ by BSA led to the further decrease of MS2 removal.